Sibu District Education Office / Natasha Minda Palis - Palis, Natasha Minda (University Technology MARA Sarawak, 2021)
The Sibu District Education Office began construction in 1949 at the same location as the Sibu District Office. After four years in that facility, the Sibu District Education Office was shifted to the Lau King Howe Dispensary building, where they remained active until 1976. In mid-year, this office was relocated and operated at Mission Street Mission Home. Again in 1982, this office need to change their building to Wisma Persekutuan at Jalan Awang Ramli Amit until 30 June 1996. Ultimately, Sibu District Education Office was placed on the 6th floor at Wisma Persekutuan Block 3, Lot 462, Persiaran Brooke, Pekan Sibu at Teng Chin Hua Sibu road from 1 July 1996 until now. As a result, the Sibu District Education Office was one of the Sarawak State Education Department's administrative hierarchies. Dr. Maszlee Malik, our former Minister of Education, has recommended that a new structure and scope of work being implemented in order to adapt to the new norm in 2020. The Sibu District Education Office has converted all of its units into sectors. There are currently eight sectors in operation, including Sector of Professional Service Support, Planning Sector, Learning Sector, School Management Sector, Student Development Sector, Psychology and Counseling Sector, Assessment and Examination Sector, Management Sector As a result, the District Education Officer (DEO), Sibu District Deputy Education Officer, and the other ten units headed by their respective Unit Heads run the Sibu District Education Office. Additionally, these units included School Management Units, Academic Units, Human Development Management Units, Service Management Units, Development and Supply Units, Finance Units, Psychology and Counseling Units, Islamic and Moral Education Units, Information or ICT Units, and Assessment and Examination Units. As a result, the Sibu District Education Office has responsibility for 116 schools, comprising Vocational College (1), Primary School (46), Chinese Primary School (47), and Secondary School (22). The Divisional Technology Center and the Teacher Activity Center, with the assistance of their respective Heads or Coordinators, should assist the Sibu District Education Office in this regard.